Amphotericin B concentrations in healthy mallard ducks (Anas platyrhynchos) following a single intratracheal dose of liposomal amphotericin B using an atomizer. (3rd August 2017) - Phillips, Ashley; Fiorello, Christine V; Baden, Rachel M; Liu, Jack H; Burmas, Nathaniel C; Ruvalcaba, Carlos A; Monroy, Roger; Mohr, F Charles; Gehring, Ronette; Delplanque, Jean-Pierre; Clemons, Karl V; Stevens, David A; et al.
Abstract: Aspergillosis is a fungal infection that primarily affects the respiratory tract. Amphotericin B has broad antifungal activity and is commonly used to treat aspergillosis, a fungal pneumonia that is a common sequela in oiled waterfowl as well as other birds in wildlife rehabilitation. Pharmacokinetic parameters of nebulized amphotericin B in an avian model have been reported, but those of direct intratracheal delivery have yet to be established. The objective of this study was to evaluate if a single 3 mg/kg dose of liposomal amphotericin B delivered intratracheally using a commercial atomizer would achieve plasma and lung tissue concentrations exceeding targeted minimum inhibitory concentrations (MIC) for Aspergillus species in adult mallard ducks ( Anas platyrhynchos ). Following intratracheal delivery, amphotericin B was present in lung parenchyma at concentrations above the targeted MIC of 1 μg/g for up to 9 days post-administration; however, distribution of the drug was uneven, with the majority of the drug concentrated in one lung lobe. Concentrations in the contralateral lung lobe and the kidneys were above the targeted MIC 1 day after administration but declined exponentially with a half-life of approximately 2 days. Plasma concentrations were never above the targeted MIC. Histological examination of the trachea, bronchi, lungs, heart, liver, and kidneys did not reveal any toxic changes. Using a commercial atomizer, intratracheal delivery of amphotericin B at 3 mg/kg resulted in lung parenchyma concentrations above 1 μg/ml with no discernable systemic effects. Further studies to establish a system of drug delivery to both sides of the pulmonary parenchyma need to be performed, and the efficacy of this treatment for disease prevention remains to be determined.